Cara Berhukum yang Benar Bagi Profesional Hukum (Ijtihad Sebagai Terobosan Hukum Progresif) - Abdul Jamil (Jurnal Hukum IUS QUIA IUSTUM, 2008)
In the practical aspect, legal enforcement in Indonesia is still facing a controversy in terms of how a just verdict should be. The said controversy rooted deeply in the differences in the understanding towards the concept of normative law and the concept of progressive law. In the fact, most of legal apparatuses are still confined in normative law as a parameter of the verdicts that they conclude. On the other hand, from progressive law point of view, the existing legal norms are considered for not being a true reflection of the idea of justice. Consequently, the people then rely their hope for justice on the ability of lawyers to afford it